Adaptive mutability of colorectal cancers in response to targeted therapies - Russo, Mariangela; Crisafulli, Giovanni; Sogari, Alberto; Reilly, Nicole M; Arena, Sabrina; Lamba, Simona; Bartolini, Alice; Amodio, Vito; Magrì, Alessandro; Novara, Luca; Sarotto, Ivana; Nagel, Zachary D; et al. (Science (American Association for the Advancement of Science), 2019)
The emergence of drug resistance limits the efficacy of targeted therapies in human tumors. The prevalent view is that resistance is a fait accompli: when treatment is initiated, cancers already contain drug-resistant mutant cells. Bacteria exposed to antibiotics transiently increase their mutation rates (adaptive mutability), thus improving the likelihood of survival. We investigated whether human colorectal cancer (CRC) cells likewise exploit adaptive mutability to evade therapeutic pressure. We found that epidermal growth factor receptor (EGFR)/BRAF inhibition down-regulates mismatch repair (MMR) and homologous recombination DNA-repair genes and concomitantly up-regulates error-prone polymerases in drug-tolerant (persister) cells. MMR proteins were also down-regulated in patient-derived xenografts and tumor specimens during therapy. EGFR/BRAF inhibition induced DNA damage, increased mutability, and triggered microsatellite instability. Thus, like unicellular organisms, tumor cells evade therapeutic pressures by enhancing mutability.